REDESAIN INKLUSIF DAN PENINGKATAN AKSESIBILITAS LAYANAN UNTUK BERBAGAI PENGGUNA DI PERPUSTAKAAN UNIVERSITAS KRISTEN PETRA - Gunawan Tanuwidjaja; Dian Wulandari; Luciana Kristanto (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2020)
Title: Inclusive Design and Service Accessibility Improvement for Various Users in Petra Christian University Library In the context of Indonesia, Act No. 8 of 2016 actually recognizes the rights of the disabled. Unfortunately, the UNCRPD implementation seems not quite effective. Many educational facilities are not accessible for the disabled or the People with Disabilities. The learning environment has an indirect impact on student achievement, creating a positive attitude, higher motivation for learning and no doubt better performance. The accessibility aspect of learning places is crucial for educational facilities such as university Library. Petra Christian University (UKP) is located in the heart of Wonocolo District, Surabaya, East Java-Indonesia. With the motto